Microwave Assisted Solvent Free Synthesis of Azomethines from Aryl Aldehydes on Melamin Formaldehyde as Solid Support - Ramin Rezaei; Mohammad K. Mohammadi; Tahereh Ranjbar (E-Journal of Chemistry)
Various aryl aldehydes underwent prompt one pot conversion into the corresponding azomethines in high yields by reacting with hydroxylamine hydrochloride supported on melamine formaldehyde under microwave irradiation.